2015
DOI: 10.11648/j.sjph.20150303.28
|View full text |Cite
|
Sign up to set email alerts
|

NNT Elimination and the Nigeria��s Health System: Where is the Missing Link

Abstract: In 1994 when the global neonatal tetanus (NNT) elimination campaign started gaining momentum, there were 104 out of the 161 developing countries that achieved the NNT elimination in 2000 with 24 other countries close to achieving. Nigeria is among the remaining countries that are yet to achieve the global NNT elimination target as set by the WHO. Although Nigeria plays a strategic role on the African continent, the government has failed to uphold the goals of the universal basic primary health care; this made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Client satisfaction is an integral component of health service. The effectiveness of health care is determined to some degree by consumer's satisfaction with service provided and its quality the missing link (1,14). The study conducted in rural Bangladesh showed that the most powerful predictor for client satisfaction was provider behaviour, especially respect, politeness and reduction in waiting time (15).…”
Section: Introductionmentioning
confidence: 99%
“…Client satisfaction is an integral component of health service. The effectiveness of health care is determined to some degree by consumer's satisfaction with service provided and its quality the missing link (1,14). The study conducted in rural Bangladesh showed that the most powerful predictor for client satisfaction was provider behaviour, especially respect, politeness and reduction in waiting time (15).…”
Section: Introductionmentioning
confidence: 99%